Effects of different cartel policies: Evidence from the German power-cable industry - Hans-Theo Normann; Elaine S. Tan (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
We analyze the effects of cartel policies on firm behavior using data from the German power-cable cartel. Antitrust authorities affected the cartel under two different legal regimes: penalizing the cartel in some years, and exempting it for ten years from the general cartel prohibition. While penalties did not reduce prices or profits, making collusion legal raised profits by at least 16% each year, compared to the time when the illegal cartel was not prosecuted. The threat of penalties was sufficient to reduce profit from collusion. The intended efficiency gains from rationalization, which was the justification for legalizing the cartel, did not materialize.
Keywords: 330